Multivariate optimization of highway alignment using multi-criteria evaluation - Sajjadi, Seyed Mahdi (2015)
Road design and construction have a long global history of three thousand years ago. Attention to optimize the highway alignment is being increased with advancement in science and technology especially through the past two decades. The main principle aim of highway optimization is design the highway that meets all significant design criteria simultaneously, to select the best design. Considering all criteria along with technical and economical parameters is complicated and time consuming process. Traditional methods of determining optimal highway alternatives are associated with errors due to the extensive data volumes besides time consumption and it is only focused on cost criterion. Nowadays, innovative techniques are frequently applied in developed countries, while new methods are constantly being developed. This research presents a novel methodology for highway alignment optimization by using Geographic Information System (GIS) and Analytic Hierarchy Process (AHP), which can help to determine the best highway alternative according to several criteria. In the present research, these criteria were limited to cost, constraints and safety where each criterion was divided into several sub-criteria that cover all important parameters in highway alignment optimization. This methodology is implemented for a case study region in Iran (Qeydar–Zarrin Rood roadway in Zanjan province, Iran) that can also be expanded for any other territory. The final results obtained from this proposed method as compared with the existing road in the case study region indicate that the best highway alternative selected with this methodology concurrently satisfies all parameters defined for the optimization process. It does not necessarily mean that the alternative selected with the proposed methodology has the lowest cost and constraints as well as optimum safety separately, but it can acquire acceptable value related to the cost, constraints and safety parameters based on their weights better than other alternatives. Therefore, the proposed methodology can determine the best highway alignment between two points considering the effect of all the used criteria concurrently.